Releasing trapped minds the strategic role of managers in improving productivity in organisations - Tan, Victor S. L. (Pelanduk Publications, 2000)
"Releasing Trapped Minds" is certainly imperative for leaders and executives who want their organisations to be progressive and successful. This book provides a detailed guide on how to get the best out of people and how to release trapped minds to improve the productivity and profitability of organisations.